PENGUATAN FUNGSI PENGAWASAN DEWAN PERWAKILAN DAERAH DALAM RANGKA PROSES DEMOKRATISASI DI TINGKAT LOKAL - Yusuf Wibisono (Jurnal Ilmu dan Budaya, 2017)
In the framework of the autonomy system of the region, the existence People's Representative Council of Region (DPRD) became very important. The autonomy basically wanted the existence of utilization of the local community, where all the aspirations and the interests of the community would be articulated by DPRD, and will be aggregated through the policy in the form of the regional regulation. This DPRD will be representative for the need of people in order to fight for all the aspirations of the community that was formed in the regional regulation and DPRD policies. So that in the autonomy discourse of the region, the DPRD function that was directly linked to the existence of the community was the function of the controlling. However from several results of the research that was carried out, mentioned that the function of the DPRD does not meet the hope of the community, both the quantity and the quality of the regional regulation (Regional Regulations) that was produced by DPRD. Because of their poor achievement, the community's trust continually decreases towards the work of DPR. This condition automatically became to be a bad precedent for the autonomy system of the region and the process of democratization in the local level. Because of that from time to time, DPRD must carry out the improvement of the achievement in the legislative function.